Internal and External Factors Influencing Forgiveness Among Adolescents: A Literature Review - Maria Ignasia Beto Larantukan; Yohana Fransiska Glalan; Maria Leliyanti Bura (Journal of Psychology and Education Counseling (JPEC), 2026)
Forgiveness is an important component of adolescents’ social and emotional development, as it helps individuals cope with interpersonal conflicts, maintain social relationships, and enhance psychological well-being. This study aimed to identify and analyze the internal and external factors influencing forgiveness among adolescents. A literature review method was employed using data sources retrieved from the Garuda database and Google Scholar. The literature search was conducted using keywords related to adolescent forgiveness and its influencing factors. The reviewed studies consisted of articles published between 2016 and 2026. The initial search identified 30 articles, which were subsequently screened based on predetermined inclusion and exclusion criteria, resulting in 14 articles being selected for further analysis. The findings were analyzed using a descriptive qualitative approach and classified into internal and external factors. The review revealed that internal factors associated with adolescents’ willingness to forgive included empathy, religiosity, emotional maturity, humility, personality, ego, rumination, and individual personal characteristics. Meanwhile, the identified external factors included peer social support, interpersonal communication, attachment, friendship quality, family conflict, relationship closeness, commitment, relationship satisfaction, and apology. The findings indicated that empathy and religiosity were the most frequently identified internal factors, whereas the quality of interpersonal relationships emerged as the most prominent external factor. Overall, the findings suggest that adolescent forgiveness is shaped by the interplay between individual characteristics and the surrounding social environment.